Sugars in peach fruit: a breeding perspective. (20th January 2016) - Cirilli, Marco; Bassi, Daniele; Ciacciulli, Angelo
Abstract: The last decade has been characterized by a decrease in peach ( Prunus persica ) fruit consumption in many countries, foremost due to unsatisfactory quality. The sugar content is one of the most important quality traits perceived by consumers, and the development of novel peach cultivars with sugar-enhanced content is a primary objective of breeding programs to revert the market inertia. Nevertheless, the progress reachable through classical phenotypic selection is limited by the narrow genetic bases of peach breeding material and by the complex quantitative nature of the trait, which is deeply affected by environmental conditions and agronomical management. The development of molecular markers applicable in MAS or MAB has become an essential strategy to boost the selection efficiency. Despite the enormous advances in 'omics' sciences, providing powerful tools for plant genotyping, the identification of the genetic bases of sugar-related traits is hindered by the lack of adequate phenotyping methods that are able to address strong within-plant variability. This review provides an overview of the current knowledge of the metabolic pathways and physiological mechanisms regulating sugar accumulation in peach fruit, the main advances in phenotyping approaches and genetic background, and finally addressing new research priorities and prospective for breeders. Abstract : Fruit crops: Peach breeders aim for sweet success Understanding the physiology and genetics of sugar accumulation in peaches is essential to breeding sweeter, more popular fruit. Peach ( Prunus persica ) is one of the most difficult fruit crops to improve by breeding, thanks to limited genetic variability and a lack of information on the genetic basis of complex traits. Declining sales of peaches are thought to result from poor flavor, a trait combining taste, aroma and mouth-feel. Daniele Bassi and colleagues at the University of Milan, Italy, review the current state of knowledge in peach breeding, including the physiological causes of flavor variation, and the potential for improvement using traditional or modern methods. They find that sugar content does not always correlate directly with consumer preference, and is dependent on a range of factors including genetics, environment and cultivation techniques.